PRESTASI BELAJAR SISWA MATEMATIKA DALAM PEMBELAJARAN JARAK JAUH DITINJAU DARI MOTIVASI BELAJAR - Sukiyanto; Syamsulrizal; Dewi Anggreini; Ahmad Isroil (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2022)
Motivation for learning is one of the things that need to be raised in school learning efforts. This study aims to detail students' mathematics learning motivation in distance learning. This research uses quantitative research, while this type uses survey methods. The subject of the study was a private high school student in Lamongan, East Java. The instrument used in the study was a survey using a questionnaire made in google form. The student learning motivation survey results, including the criteria of each excellent indicator, found the highest score, namely 90.44%, on the enthusiastic indicator. In comparison, the good indicator found the lowest score of 71.61%.